Efficacy and Safety of Subcutaneous Unfractionated Heparin Administered Every 8 hours for Venous Thromboembolism Prophylaxis in Reconstructive Head and Neck Tumor Patients: A Systematic Review and 6-Year Institutional Case Series - Cevik, Jevan; Newland, David P.; Cheong, Edward; Cabalag, Miguel; Ramakrishnan, Anand (Journal of Reconstructive Microsurgery, 2024)
Patients with head and neck tumors undergoing free flap reconstructions are at high risk of postoperative venous thromboembolism (VTE). To date, no specific guidelines are available regarding VTE prophylaxis in this patient group. This study aims to contribute to this scarcity of information by reviewing the literature regarding anticoagulation regimens in this patient group and evaluating the efficacy and safety of postoperative subcutaneous heparin dosed at 5,000 units every 8 hours routinely utilized at our institution.PubMed and Embase databases were searched from inception until November 2023. Data were collected and levels of evidence were evaluated according to the Oxford Centre for Evidence Based Medicine guidelines. Additionally, a retrospective review of all patients with head and neck tumors undergoing free tissue transfer at our institution between 2015 and 2021 was performed. Patients were restricted to those receiving 5,000 units of subcutaneous heparin every 8 hours postoperatively. Key outcomes included rates of VTE and surgical site hematoma.This systematic review found 15 studies eligible for inclusion ranging from 1998 to 2023. Anticoagulation regimens were markedly heterogenous. Among the literature, VTE rates reported ranged from 0 to 9.6% and bleeding rates ranged between 3.5 and 29%. Our 6-year institutional analysis revealed 393 total patients. Overall, three episodes of VTE were identified (0.76%) consisting of one deep vein thrombosis and two pulmonary emboli. The overall rate of hematoma was 9.4% with a higher rate of hematoma at the recipient site (8.1%) than the donor site (1.3%).When compared with the existing literature this study found a low rate of VTE and a comparable incidence postoperative hematoma. This suggests that 5,000 units of subcutaneous heparin given every 8 hours may be a safe and effective postoperative anticoagulation regimen for these patients.
Keywords: anticoagulation; free flap; hematoma; head and neck cancer; venous thromboembolism